Presidential Decree on Legal Protection for Advocates: A Neglected Pillar of Justice in a State Based on the Rule of Law - A. Muhammad Hasgar; Amir Sohail (Global Journal of Law, AI & Ethics, 2026)
In a state based on the rule of law, the existence of advocates as one of the pillars of law enforcement should be firmly guaranteed by the state. However, in practice, advocates often experience criminalization, intimidation, and even violence while carrying out their professional duties, especially when assisting vulnerable groups or handling cases that overlap with power. The background of this problem encourages the importance of the Presidential Regulation (Perpres) on Legal Protection for Advocates as a concrete effort by the state to protect the advocacy profession as part of a fair justice system. The formulation of the problem in this study is: Why is legal protection for advocates still weak in practice? and What is the urgency of establishing a Perpres as an instrument of legal protection for advocates in the context of a state based on the rule of law? The method used is normative juridical with a statute approach, a conceptual approach, and a case approach to the criminalization of advocates. The results of the discussion indicate that the weak protection of advocates is caused by the lack of implementation of the norms of Article 16 of the Advocates Law, the absence of a mechanism for enforcing immunity rights, and the absence of derivative regulations that are binding on law enforcement officers. In conclusion, the formation of a Presidential Regulation is a strategic and urgent step to ensure that advocates are protected institutionally, while strengthening their position in upholding justice and human rights. Without concrete protection, the rule of law risks losing an important pillar in its justice system